Deregulated expression of cytoskeleton related genes in the spinal cord and sciatic nerve of presymptomatic SOD1G93A Amyotrophic Lateral Sclerosis mouse model - Maximino, Jessica R.; de Oliveira, Gabriela P.; Alves, Chrystian J.; Chadi, Gerson (Frontiers in Cellular Neuroscience, 2014)
Early molecular events related to cytoskeleton are poorly described in Amyotrophic Lateral Sclerosis (ALS), especially in the Schwann cell (SC), which offers strong trophic support to motor neurons. DAVID tool identified cytoskeleton-related genes by employing the Cellular Component Ontology (CCO) in a large gene profiling of lumbar spinal cord and sciatic nerve of presymptomatic SOD1G93A mice. One and five CCO terms related to cytoskeleton were described from the spinal cord deregulated genes of 40 days (actin cytoskeleton) and 80 days (microtubule cytoskeleton, cytoskeleton part, actin cytoskeleton, neurofilament cytoskeleton and cytoskeleton) old transgene mice, respectively. Also, four terms were depicted from the deregulated genes of sciatic nerve of 60 days old transgenes (actin cytoskeleton, cytoskeleton part, microtubule cytoskeleton and cytoskeleton). Kif1b was the unique deregulated gene in more than one studied region or presymptomatic age. The expression of Kif1b (qPCR) elevated in the lumbar spinal cord (40 days old) and decreased in the sciatic nerve (60 days old) of presymptomatic ALS mice, results that were in line to microarray findings. Upregulation (24.8 fold) of Kif1b was seen in laser microdissected enriched immunolabeled motor neurons from the spinal cord of 40 days old presymptomatic SOD1G93A mice. Furthermore, Kif1b was dowregulated in the sciatic nerve Schwann cells of presymptomatic ALS mice (60 days old) that were enriched by means of cell microdissection (6.35 fold), cell sorting (3.53 fold) and primary culture (2.70 fold) technologies. The gene regulation of cytoskeleton molecules is an important occurrence in motor neurons and Schwann cells in presymptomatic stages of ALS and may be relevant in the dying back mechanisms of neuronal death. Furthermore, a differential regulation of Kif1b in the spinal cord and sciatic nerve cells emerged as key event in ALS.